SOCIAL MARKS OF OUR TIMES: GENDER, SEXUALITY AND SCHOOL EDUCATION - Lucifora, Cristiane de Assis [UNESP]; Reina, Fabio Tadeu [UNESP]; Muzzeti, Luci Regina [UNESP]; Silva, Renan Antonio da [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
This article had as its starting point a chapter of the Master Dissertation entitled The reproduction of gender inequalities in marvelous fairy tales as circumscribed marks in Pre-school Education defended in February 2017 on the problematization of the social roles attributed to the gender of the birth of the subjects and the various constructions attributed as inherent, being present in several areas, among them the school. The theoretical field that underlies the research undertaken in the master's degree and that is present in this article is the Critical Theory having as main theoretical Pierre Bourdieu and its categories of analysis. This article presents as a theoretical reflexive strategy on how much gender inequalities are still present and that the idea of overcoming often reinforces the idea that opportunities are for everyone and that many are not present because they do not want or strive hard enough.
Keywords: Gender; Sexuality; Education